Hydrophilic magnetic polymer as well as preparation method and application thereof

By preparing the hydrophilic magnetic polymer (HMP) of the preparing mesh pore structure, the problem of low efficiency of existing magnetic polymers in water in the water has been solved, and the efficient and rapid separation of antibiotics in the tail water in aquaculture is realized.

CN119371678AActive Publication Date: 2025-01-28FISHERIES RESEARCH INSTITURE OF FUJIAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411708237.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-28
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing magnetic polymer materials perform best in non-aqueous environments and cannot effectively adsorb antibiotics in water, and the scope of application is narrow.

Method used

The preparation method of hydrophilic magnetic polymer (HMP) is used to react with 3-amino-1,2,4-triazol and magnetic hydroxide in the ionic water to form a mesh pore structure of hydrophilic water Sexual magnetic polymer.

Benefits of technology

HMP shows the ability of efficient adsorption antibiotic drugs in water. In particular, it has a significant adsorption effect on pyrone and tetracycline drugs. The adsorption rate is fast. It can achieve adsorption balance within 120s to 150s, and the efficiency can reach more than 65 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371678A_ABST
    Figure CN119371678A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophilic magnetic polymer and a preparation method and application thereof.The preparation method of the hydrophilic magnetic polymer comprises the steps that 3-amino-1, 2, 4-triazole is dissolved in deionized water, and a 3-amino-1, 2, 4-triazole aqueous solution is obtained; adding the magnetic iron-aluminum mixed hydroxide into deionized water, continuously stirring to form a suspension, adding a 3-amino-1, 2, 4-triazole aqueous solution, continuously stirring for a period of time, adding a cross-linking agent, continuously stirring for a period of time, and adding an initiator to obtain a mixture; transferring the mixture to an inert atmosphere environment, carrying out water bath at 35-45 DEG C, and carrying out polymerization reaction under a stirring condition; and after the reaction is finished, collecting a product by using a magnet, and washing to obtain the hydrophilic magnetic polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aquaculture tail water treatment and relates to a hydrophilic magnetic polymer and a preparation method and application thereof. Background Art

[0002] China is a major aquaculture country with rich fishery resources. According to the China Fisheries Statistical Yearbook, in 2023, China's total aquaculture output was 58.0961 million tons, a year-on-year increase of 4.39%. The rapid development of the aquaculture industry has also brought about environmental pollution problems such as aquaculture tailwater discharge that cannot be ignored. The large-scale use and even abuse of antibiotics in aquaculture, as well as inefficient treatment, not only deteriorate the environment of aquaculture waters, leading to drug resistance in fish, shrimps and crabs, but also aquaculture tailwater has become one of the main sources of antibiotics in surface waters.

[0003] Common antibiotics in aquaculture tailwater include macrolide antibiotics (MAs), quinolone antibiotics (QNs), sulfonamide antibiotics (SAs), tetracycline antibiotics (TCs), etc. In recent years, relevant research institutions at home and abroad have proposed to use physical elimination, photodegradation, chemical oxidation, microbial degradation, phytoremediation and other methods to carry out antibiotic management. Among them, adsorption is a commonly used method for removing antibiotics in wastewater treatment. Traditional activated carbon adsorbents have the disadvantages of large dosage and difficulty in subsequent separation. Therefore, it is very important to strengthen the development of new aquaculture tailwater antibiotic adsorbents.

[0004] Magnetic polymer materials have the characteristics of large specific surface area and magnetism, which can achieve large-scale adsorption and rapid separation. However, most common magnetic polymer materials are synthesized in non-polar organic solvents and only show optimal performance in non-aqueous environments. They are not suitable for the adsorption of antibiotics in aqueous media and have a narrow scope of application. In order to overcome this limitation, hydrophilic magnetic polymer materials (HMP) have become a research hotspot in recent years. Summary of the invention

[0005] The present disclosure provides a hydrophilic magnetic polymer and a preparation method and application thereof, which can effectively solve the above problems.

[0006] The present disclosure is implemented as follows:

[0007] In a first aspect, the present disclosure provides a method for preparing a hydrophilic magnetic polymer, the preparation method comprising:

[0008] Dissolving 3-amino-1,2,4-triazole in deionized water to obtain an aqueous solution of 3-amino-1,2,4-triazole;

[0009] Adding the magnetic mixed hydroxide into deionized water, stirring continuously, adding the 3-amino-1,2,4-triazole aqueous solution after forming a suspension, continuing stirring for a period of time, then adding the crosslinking agent, continuing stirring for a period of time, and then adding the initiator to obtain a mixture;

[0010] The mixture is transferred to an inert atmosphere environment, and a polymerization reaction is carried out in a water bath at 35-45° C. with stirring. After the reaction is completed, the product is collected by a magnet, and the product is washed and dried to obtain the hydrophilic magnetic polymer.

[0011] In a second aspect, the present disclosure provides a hydrophilic magnetic polymer, wherein the hydrophilic magnetic polymer has a mesh hole structure;

[0012] The hydrophilic magnetic polymer comprises:

[0013] A magnetic iron-aluminum mixed hydroxide and a polymer layer coated on the surface of the magnetic iron-aluminum mixed hydroxide, wherein the polymer layer is obtained by polymerization reaction of 3-amino-1,2,4-triazole aqueous solution and dimethyl glycol acrylate;

[0014] The Fourier infrared spectrum of the hydrophilic magnetic polymer is as follows: Figure 1 shown.

[0015] In a third aspect, the present disclosure provides an application of a hydrophilic magnetic polymer in adsorbing antibiotic drugs in aquaculture tail water, wherein the antibiotic drug is at least one of quinolone drugs and tetracycline drugs.

[0016] A hydrophilic magnetic polymer obtained by the preparation method of the first aspect, or the hydrophilic magnetic polymer of the second aspect, is used in the adsorption of antibiotic drugs in aquaculture tail water, wherein the antibiotic drug is at least one of quinolone drugs and tetracycline drugs.

[0017] The beneficial effects of the present disclosure are:

[0018] The present disclosure provides a HMP and a preparation method thereof. The HMP can be synthesized in water, the synthesized HMP has strong hydrophilicity, and the preparation method is simple and easy and does not require strict experimental conditions.

[0019] Furthermore, in the HMP, the polymer layer formed on the surface of MMH is an ideal gel-type mesh pore structure with a looser spatial structure and a larger specific surface area, so that the HMP can adsorb the target molecules more fully and the internal mass transfer process is faster.

[0020] Furthermore, the magnetization intensity of the HMP reaches 7.6emu / g. Under the action of an external magnetic field, the HMP dispersed in water can be quickly separated within 10 seconds.

[0021] Furthermore, the HMP has a fast adsorption rate and can reach adsorption equilibrium in 120s to 150s, and the equilibrium adsorption amount of the antibiotic drug reaches 10.901 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 It is the FTIR graph of iron-aluminum MMH and HMP provided in the embodiments of the present disclosure.

[0024] Figure 2 For different molar ratios of Fe 2+ / Al 3+ Comparison of the yields of iron-aluminum MMH produced from reactants.

[0025] Figure 3 HMP adsorption isotherm diagram provided for the embodiments of the present disclosure.

[0026] Figure 4 This is a graph showing the adsorption kinetics of HMP according to an embodiment of the present disclosure.

[0027] Figure 5 This is a pseudo-first-order adsorption kinetics fitting diagram of HMP provided in an embodiment of the present disclosure.

[0028] Figure 6 This is a pseudo-second-order adsorption kinetics fitting diagram of HMP provided in an embodiment of the present disclosure.

[0029] Figure 7 A comparison of the adsorption amount of HMP prepared with different molar ratios of ATA / EGDMA.

[0030] Figure 8 This is a comparison chart of the adsorption amount of HMP prepared at different polymerization reaction times.

[0031] Fig. 9 XRD patterns of the iron-aluminum MMH and HMP provided in the embodiments of the present disclosure.

[0032] Fig.10In the figure, (a) is the TEM image of the iron-aluminum MMH provided in the embodiment of the present disclosure; (b) is the TEM image of the HMP (50 nm); and (c) is the TEM image of the HMP (200 nm).

[0033] Fig.11 In the figure, (a) is a SEM image of the iron-aluminum MMH provided in an embodiment of the present disclosure; (b) is a SEM image of the HMP.

[0034] Fig.12 VSM diagram of iron and aluminum MMH and HMP provided in the embodiments of the present disclosure. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure. Therefore, the following detailed description of the embodiments of the present disclosure provided in the drawings is not intended to limit the scope of the present disclosure for protection, but merely represents the selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure.

[0036] The present disclosure provides a method for preparing a hydrophilic magnetic polymer, the method comprising:

[0037] Dissolving hydrophilic 3-amino-1,2,4-triazole (ATA) in deionized water to obtain a 3-amino-1,2,4-triazole aqueous solution;

[0038] Adding magnetic mixed hydroxide (MMH) to deionized water, stirring continuously, adding 3-amino-1,2,4-triazole aqueous solution after forming a suspension, continuing stirring for a period of time, then adding a crosslinking agent, continuing stirring for a period of time, and then adding an initiator to obtain a mixture;

[0039] The mixture is transferred to an inert atmosphere environment, and a polymerization reaction is carried out in a water bath at 35-45° C. with stirring. After the reaction is completed, the product is collected by a magnet, and the product is washed and dried to obtain the hydrophilic magnetic polymer.

[0040] In some embodiments, the crosslinking agent is at least one of ethylene glycol dimethyl acrylate (EGDMA), trimethylolpropane trimethacrylate, and dimethyl hexanediol acrylate.

[0041] In some embodiments, the initiator is at least one of ammonium persulfate (APS), azobisisobutyronitrile, and potassium persulfate.

[0042] In some embodiments, the MMH is stirred until it is completely dispersed for 10 minutes to prepare an MMH suspension.

[0043] In some embodiments, stirring the MMH until it is completely dispersed comprises: stirring conditions are 450-550 r / min.

[0044] In some embodiments, after the suspension is formed, an aqueous solution of 3-amino-1,2,4-triazole is added and stirring is continued for a period of time, including: the stirring time is 30 minutes.

[0045] In some embodiments, a cross-linking agent is then added and stirring is continued for a period of time, including: stirring time of 30 minutes.

[0046] In some embodiments, the molar ratio of 3-amino-1,2,4-triazole to the cross-linking agent is 1:4.5-5.5.

[0047] In some embodiments, the molar ratio of 3-amino-1,2,4-triazole to the cross-linking agent is 1:4.8-5.2.

[0048] In some embodiments, the molar ratio of 3-amino-1,2,4-triazole to the cross-linking agent is 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9, 1:5, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5.

[0049] In some embodiments, transferring the mixture into an inert atmosphere environment includes: the inert atmosphere environment is a nitrogen atmosphere environment.

[0050] In some embodiments, the polymerization reaction is carried out in a water bath at 35-45° C. under stirring conditions, including: the stirring condition is 250-350 r / min.

[0051] In some embodiments, the polymerization reaction time is 4.5-5.5 hours.

[0052] In some embodiments, the polymerization reaction time is 4.8-5.2 hours.

[0053] In some embodiments, the polymerization reaction time is 4.5 h, 4.6 h, 4.7 h, 4.8 h, 4.9 h, 5 h, 5.1 h, 5.2 h, 5.3 h, 5.4 h, or 5.5 h.

[0054] In some embodiments, the product is washed and then dried, comprising: drying at 80° C. for 5 hours.

[0055] In some embodiments, the product is washed and then dried to obtain the hydrophilic magnetic polymer, comprising: sieving the dried product through a 150-mesh standard test sieve to obtain the hydrophilic magnetic polymer having a diameter greater than 0.1 mm.

[0056] Materials with too small a diameter will float on the water surface, which is not conducive to subsequent separation.

[0057] In some embodiments, the magnetic mixed hydroxide is a magnetic iron-aluminum mixed hydroxide.

[0058] In some embodiments, the method for preparing the magnetic iron-aluminum mixed hydroxide comprises:

[0059] Ammonium ferrous sulfate hexahydrate and aluminum chloride hexahydrate are completely dissolved in deionized water, and then an alkaline solution is added to adjust the pH value of the solution to 9.5-10.5, and a coprecipitation reaction is carried out under stirring conditions. After the reaction is completed, the product is collected by a magnet, and the product is washed to obtain the magnetic iron-aluminum mixed hydroxide.

[0060] In some embodiments, adding an alkaline solution to adjust the pH value of the solution to 9.5-10.5 includes: adding an alkaline solution to adjust the pH value of the solution to 10.

[0061] In some embodiments, the coprecipitation reaction is carried out under stirring conditions, including: stirring at 450-550 r / min for 10 min.

[0062] In some embodiments, the alkaline solution is an aqueous NaOH solution.

[0063] In some embodiments, the co-precipitation reaction is carried out using a low supersaturation co-precipitation method.

[0064] In some embodiments, the molar ratio of ammonium ferrous sulfate hexahydrate to aluminum chloride hexahydrate is not less than 2:1.

[0065] In some embodiments, the molar ratio of ammonium ferrous sulfate hexahydrate to aluminum chloride hexahydrate is 2-3:1.

[0066] In some embodiments, the molar ratio of ammonium ferrous sulfate hexahydrate to aluminum chloride hexahydrate is 2:1, 2.2:1, 2.4:1, 2.6:1, 3:1, 3.5:1, or 4:1.

[0067] In some embodiments, after the reaction is completed, the reaction is allowed to stand and the layers are separated, the supernatant is discarded, and the black product is collected by a magnet.

[0068] In some embodiments, an appropriate amount of deionized water with a pH value of 7 is added to the upper layer of the magnetic iron-aluminum mixed hydroxide and stored at room temperature for later use.

[0069] An embodiment of the present invention provides a hydrophilic magnetic polymer, wherein the hydrophilic magnetic polymer has a mesh hole structure;

[0070] The hydrophilic magnetic polymer comprises:

[0071] A magnetic iron-aluminum mixed hydroxide and a polymer layer coated on the surface of the magnetic iron-aluminum mixed hydroxide, wherein the polymer layer is obtained by polymerization reaction of 3-amino-1,2,4-triazole aqueous solution and dimethyl glycol acrylate;

[0072] The Fourier infrared spectrum of the hydrophilic magnetic polymer is as follows: Figure 1 shown.

[0073] An embodiment of the present invention provides an application of the hydrophilic magnetic polymer in any of the above embodiments in adsorbing antibiotic drugs in aquaculture tail water, wherein the antibiotic drug is at least one of quinolone drugs and tetracycline drugs.

[0074] In some embodiments, the antibiotic drug is a tetracycline drug.

[0075] In some embodiments, the tetracycline drug includes at least one of doxycycline, oxytetracycline, and tetracycline.

[0076] In some embodiments, the quinolone drug includes at least one of danofloxacin, nalidixic acid, ciprofloxacin, difloxacin, sparfloxacin, pipemidic acid, ofloxacin, flumequine, enoxacin, sarafloxacin, norfloxacin, pefloxacin, enrofloxacin, fleroxacin, lomefloxacin, orbifloxacin, and marbofloxacin.

[0077] In some embodiments, the antibiotic drug is a quinolone drug.

[0078] In some embodiments, the quinolone drug includes at least one of danofloxacin, nalidixic acid, ciprofloxacin, difloxacin, sparfloxacin, pipemidic acid, ofloxacin, flumequine, and enoxacin.

[0079] In some embodiments, the concentration of the antibiotic drug is no less than 0.8 μg / mL.

[0080] In some embodiments, the antibiotic drug has a concentration of 0.8-1.2 μg / mL.

[0081] In some embodiments, the concentration of the antibiotic drug is 0.8 μg / mL, 0.9 μg / mL, 1 μg / mL, 1.1 μg / mL, or 1.2 μg / mL.

[0082] Chemicals and reagents

[0083] Ethylene glycol dimethyl acrylate (EGDMA, GR grade, Guangdong Wengjiang Chemical Reagent Co., Ltd.); trimethylolpropane trimethacrylate (purity 95%, Shanghai MacLean Biochemical Technology Co., Ltd.); dimethyl hexanediol acrylate (HPLC, Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.); 3-amino-1,2,4-triazole (ATA, purity 96%, Shanghai Aladdin Reagent Co., Ltd.); ammonium persulfate (APS, purity 99.99%, Shanghai Aladdin Reagent Co., Ltd.); azobisisobutyronitrile (purity 98%, Shanghai Aladdin Reagent Co., Ltd.); potassium persulfate (purity 99.5%, Shanghai Aladdin Reagent Co., Ltd.); iron (II) ammonium sulfate hexahydrate ((NH4)2Fe(SO4) 2· 6H2O, purity 99.99%, Shanghai Aladdin Reagent Co., Ltd.); aluminum chloride hexahydrate (AlCl 3· 6H2O, purity 99.99%, Shanghai Aladdin Reagent Co., Ltd.); sodium hydroxide (NaOH, AR grade, Xilong Scientific Co., Ltd.); sodium dihydrogen phosphate (AR grade, Xilong Scientific Co., Ltd.); acetonitrile (chromatographic grade, Merck, Germany), methanol (chromatographic grade, Fisher Scientific, UK), formic acid (AR grade, Merck, Germany) and glacial acetic acid (AR grade, Shanghai Aladdin Reagent Co., Ltd.); Oasis HLB solid phase extraction column (200 mg / 6 mL, Waters Company, USA).

[0084] Sulfapyridine, Sulfadiazine, Sulfamethoxazole, Sulfathiazole, Sulfamerazine, Sulfisoxazole, Sulfamethizol, Sulfamethazine, Sulfameter, Sulfachloropyridazine, Sulfachinoxalin, Sulfadoxine, Sulfadimethoxine, purity greater than 95%; Pipemidic acid, Nalidixic acid, Oxolinic acid acid), Flumequine, Norfloxacin, Ciprofloxacin, Enrofloxacin, Fleroxacin, Enoxacin, Pefloxacin, Lomefloxacin hydrochloride, Danofloxacin mesylate, Ofloxacin, Sparfloxacin, Difloxacin hydrochloride, Cinoxacin, Orbifloxacin, Marbofloxacin, with a purity greater than 92%; Sarafloxacin hydrochloride, with a purity greater than 87%; Oxytetracycline hydrochloride hydrochloride), tetracycline hydrochloride, doxycycline hydrochloride, with a purity greater than 90%, were purchased from Manhage (Shanghai) Biotechnology Co., Ltd. The above standards were prepared into 200 μg / mL standard stock solutions with methanol and stored at -20°C in the dark (the weight of the standard is the corrected weight, equivalent to 200 μg / mL of each active ingredient).Then, methanol was used to prepare 20 μg / mL sulfonamide antibiotic standard mixed solution, 20 μg / mL quinolone antibiotic standard mixed solution, and 20 μg / mL tetracycline antibiotic standard mixed solution, and stored at -20°C in the dark.

[0085] Taking the tetracycline antibiotic standard mixture as an example, the tetracycline antibiotic standard mixture includes all the antibiotic drugs under the tetracycline antibiotics in the above standard products, namely, oxytetracycline hydrochloride, tetracycline hydrochloride and doxycycline hydrochloride. And the concentration of each antibiotic drug contained in the antibiotic standard mixture is the same, which is 20μg / mL.

[0086] Instruments and Equipment

[0087] TSQ Quantum Ultra high performance liquid chromatography-tandem mass spectrometer equipped with electrospray ion source (ThermoFisher Scientific (FEI) Company, USA), IRAffinity-1 Fourier transform infrared spectrometer (Shimadzu Corporation, Japan), Nova Nano SEM scanning electron microscope (Thermo Fisher Scientific (FEI) Company, USA), Talos F200s transmission electron microscope (Thermo Fisher Scientific (FEI) Company, USA), 7410 vibrating sample magnetometer (LakeShore Company, USA), LC-ES-60SH mechanical stirrer (Shanghai Lichen Bangxi Instrument Technology Co., Ltd.), MS3 vortex mixer (IKA Company, Germany), LC-WB-2 constant temperature water bath (Shanghai Lichen Bangxi Instrument Technology Co., Ltd.), MT008-C vacuum glove box (Changsha Miqi Instrument Equipment Co., Ltd.), DHG-9245A electric heating blast drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.), Milli-Q water purification system, 150 mesh standard test sieve (Shangyu Yinhe Testing Instrument Factory).

[0088] HPLC-MS / MS conditions

[0089] Chromatographic conditions: CAPCELL PAK-MGⅡC18 chromatographic column (2.1mm×150mm×5μm); column temperature 35°C; flow rate 0.25mL / min; injection volume 5μL; mobile phase: A is 0.005mol / L ammonium acetate-0.1% formic acid aqueous solution, B is 0.1% formic acid methanol; elution gradient: 0-5min (10%-90% B), 5-9min (90%-100% B), 9-10min (100%-10% B), 10-15min (10% B).

[0090] Mass spectrometry conditions: electrospray ion source, positive ion detection mode, spray voltage: 3500 V, sheath gas pressure 241 KPa, auxiliary gas pressure: 2 L / min, ion transfer capillary temperature: 320 °C, selected reaction monitoring (SRM), parent ion, product ion and collision energy are listed in Table 1, Q1 half peak width: 0.7u, Q3 half peak width: 0.7u, collision gas pressure: argon, 0.2Pa.

[0091] Table 1 Selected reaction monitoring parent ions, product ions and collision energies

[0092]

[0093] Note: “*” indicates quantitative ion.

[0094] Examples 1-3

[0095] Preparation of Fe-Al MMH

[0096] Iron-aluminum MMH was prepared by low supersaturation co-precipitation method at room temperature.

[0097] Weigh (NH4)2Fe(SO4)2·6H2O and 2.41g (10mmol) AlCl3·6H2O, add them to 400mL deionized water, stir mechanically until they are completely dissolved. Then quickly add 50mL 3mol / L NaOH aqueous solution to keep the pH value at about 10. Stir mechanically at 500r / min for 10min. After the reaction is completed, stand and separate, discard the supernatant, collect the black product with a magnet, and wash it three times with 400mL deionized water to obtain FeAlMMH.

[0098] Among them, in Examples 1-3, the amounts of (NH4)2Fe(SO4)2·6H2O used are 11.76 g (30 mmol), 7.84 g (20 mmol) and 3.92 g (10 mmol), respectively.

[0099] The prepared iron-aluminum MMH was transferred to a 50 mL wide-mouth bottle, an appropriate amount of deionized water with a pH value of 7 was added to the upper layer, and stored at room temperature for later use.

[0100] The product after magnetic separation and washing in Example 1-3 was freeze-dried and its yield was weighed.

[0101] Different molar ratios of Fe 2+ / Al 3+ Impact on the production of iron and aluminum MMH Figure 2 As shown, when the molar ratio increases to 2:1, the iron-aluminum MMH production is basically constant.

[0102] Embodiment 4-8

[0103] Preparation of HMP

[0104] Weigh 10±0.02 g of the iron-aluminum MMH prepared in Example 2 into a 250 mL wide-mouth conical flask, add 100 mL of deionized water, and mechanically stir at 500 r / min until completely dispersed, continue for 10 min, and prepare an iron-aluminum MMH suspension.

[0105] Weigh 336.3 mg (4 mmol) of ATA into a 250 mL conical flask, dissolve it with 100 mL of deionized water, and add it to the wide-mouthed triangular flask after it is completely dissolved. Continue mechanical stirring for 30 minutes, then add the crosslinker EGDMA, continue stirring for 30 minutes under the same conditions, and then quickly add 1.00 g of initiator APS. The mixture is transferred to a vacuum glove box pre-filled with nitrogen, and the polymerization reaction is carried out for 5 hours in a 40°C water bath at 300 r / min. After the reaction is completed, the supernatant is discarded, the product is collected, and the product is washed 3 times with 100 mL of deionized water. Then dry it at 80°C for 5 hours, and the dried product is sieved with a standard test sieve of 150 mesh (aperture 0.1 mm) to obtain HMP with a diameter greater than 0.1 mm, which is stored at room temperature for later use.

[0106] Among them, in Examples 4-8, the amounts of the crosslinking agent EGDMA used were 2.28 mL (12 mmol), 3.04 mL (16 mmol), 3.8 mL (20 mmol), 4.56 mL (24 mmol) and 5.32 mL (28 mmol), respectively.

[0107] Examples 9-12

[0108] The difference between Examples 9-12 and Example 6 is that the polymerization reaction times are 3h, 4h, 6h and 7h respectively.

[0109] The products after magnetic separation and washing in Examples 6 and 9-12 were freeze-dried and weighed to obtain their yields. It was found that the HMP yield gradually increased with the increase of polymerization time, and the HMP yield tended to be stable after the polymerization time reached 6 hours.

[0110] Example 10

[0111] Static adsorption experiment

[0112] 10 mL of deionized water was measured and placed in a 50 mL test tube, and the standard mixed solution of sulfonamide antibiotics, the standard mixed solution of quinolone antibiotics, and the standard mixed solution of tetracycline antibiotics were added to prepare a mixed antibiotic solution. The concentrations of various antibiotic drugs in the mixed antibiotic solution are listed in Table 2.

[0113] Table 2 Concentrations of various antibiotics in mixed antibiotic solutions

[0114]

[0115]

[0116] The pH value of the solution was adjusted to 6-8, and then 5 mg of HMP prepared in Example 6 was added, and vortexed at 2000 r / min for 120 s. The supernatant was obtained by magnetic separation, and the pH value of the supernatant was adjusted to 4 with 3% by mass formic acid solution.

[0117] Take 1 mL of supernatant, add 0.25 mL of methanol, vortex mix at 2000 r / min for 30 s, pass through a 0.22 μm filter membrane, and detect by HPLC-MS / MS, with the determination repeated three times.

[0118] Calculate the adsorption amount Q. The adsorption amount calculation formula (1) is as follows:

[0119]

[0120] Where V (mL) is the volume of the solution, m (mg) is the mass of the adsorbent HMP, C0 and C e (μg / mL) are the initial concentration and equilibrium concentration of the solution, respectively.

[0121] In order to truly simulate the conditions of actual aquaculture tail water, the pH of the simulated solution was adjusted to be consistent with the pH of the tail water (pH 6-8), and the simulated solution contained sulfonamides, quinolones, and tetracyclines commonly found in aquaculture tail water. Under these conditions, a static adsorption experiment of multiple drugs was carried out to investigate the selectivity of the adsorption material.

[0122] Under the conditions of constant temperature and pH value of 6-8, the adsorption amount of HMP in solutions of sulfonamides, quinolones and tetracyclines with different mass concentrations was determined respectively.

[0123] The experimental results show that HMP cannot effectively adsorb sulfonamides, but with the increase of initial drug concentration, the adsorption of quinolones and tetracyclines by HMP gradually increases.

[0124] like Figure 3 As shown in the figure, when the drug concentration increases to 0.8 μg / mL, the adsorption of quinolones and tetracyclines by HMP tends to saturation, the adsorption capacity reaches the maximum, and the equilibrium adsorption amount Q is 10.901 mg / g. This may be because the higher initial concentration provides a stronger driving force for quinolones and tetracyclines, overcoming the mass transfer resistance between the solid and liquid phases, thereby increasing the contact time and collision number of quinolones and tetracyclines with the adsorbent, and increasing the chance of binding with the active sites of HMP.

[0125] like Figure 3 As shown in the figure, there are significant differences in the equilibrium adsorption capacity of HMP for each drug. Specifically: Q 多西环素(1.460mg / g)>Q 土霉素 (1.211mg / g)>Q 四环素 (0.856mg / g)>Q 达氟沙星 (0.749mg / g)>Q 萘啶酸 (0.694mg / g)>Q 环丙沙星 (0.633mg / g)>Q 二氟沙星 (0.616mg / g)>Q 司帕沙星 (0.581mg / g)>Q 吡哌酸 (0.576mg / g)>Q 氧氟沙星 (0.530mg / g)>Q 氟甲喹 (0.521mg / g)>Q 依诺沙星 (0.509mg / g)>Q 沙拉沙星 (0.417mg / g)>Q 诺氟沙星 (0.365mg / g)>Q 培氟沙星 (0.291mg / g)>Q 恩诺沙星 (0.264mg / g)>Q 氟罗沙星 (0.243mg / g)>Q 洛美沙星 (0.227mg / g)>Q 奥比沙星 (0.192mg / g)>Q 马波沙星 (0.181mg / g).

[0126] This shows that when the pH value of aquaculture tail water is between 6 and 8, HMP has the characteristic of preferentially adsorbing tetracyclines and quinolones. In contrast, HMP basically does not adsorb sulfonamides, and its adsorption capacity for tetracyclines is significantly better than that for quinolones.

[0127] Dynamic adsorption experiment

[0128] 10 mL of deionized water was measured in a 50 mL test tube, and mixed standard solutions of quinolone and tetracycline antibiotics were added respectively to prepare a mixed antibiotic solution with a concentration of 0.50 μg / mL for both quinolone and tetracycline antibiotics. The pH of the solution was adjusted to neutral, 5 mg of HMP prepared in Example 6 was added, and the mixture was vortexed at 2000 r / min for 10 s, 30 s, 60 s, 90 s, 120 s, 150 s and 180 s respectively. The supernatant was obtained by magnetic separation, and the pH value of the supernatant was adjusted to 4 with a formic acid solution having a mass fraction of 3%.

[0129] Take 1 mL of supernatant, add 0.25 mL of methanol, vortex mix at 2000 r / min for 30 s, pass through a 0.22 μm filter membrane, and detect by HPLC-MS / MS. The determination is repeated three times to calculate the adsorption amount Q.

[0130] In order to further evaluate the adsorption mechanism, the adsorption kinetics of quinolones and tetracyclines on HMP were studied. The experimental data were fitted with the two most common kinetic models, namely the pseudo-first-order equation and the pseudo-second-order equation. The mathematical expressions of these two models are shown in equations (2) and (3).

[0131] ln(Q e -Q t )=lnQ e -k1t (2)

[0132]

[0133] Among them, Q e and Q t are the amount of drug adsorbed on HMP at equilibrium and time t(s), respectively, k1 is the first-order rate constant (g / mg / s), and k2 is the second-order rate constant (g / mg / s).

[0134] In order to investigate the saturation adsorption time of HMP for quinolones and tetracyclines, dynamic adsorption experiments were conducted. The results are as follows: Figure 4 As shown in the figure, the kinetic adsorption curve shows a trend of gradually increasing first and then stabilizing. This shows that in the early stage of adsorption, the adsorbent has abundant active sites and can quickly bind to the drugs in the aquaculture tail water. As the adsorption proceeds, the solution concentration decreases, the number of sites on the adsorbent that have not yet bound to the drug decreases, and the adsorption rate decreases. It is worth noting that the adsorbent can reach the adsorption equilibrium state within 120-150s, which shows that its adsorption rate for quinolones and tetracyclines is very fast.

[0135] Figure 5 and Figure 6 They are the fitting diagrams obtained using the kinetic model, and the kinetic parameters obtained after processing are shown in Table 3.

[0136] Table 3 Adsorption kinetics fitting parameters

[0137]

[0138]

[0139] As shown in Table 3, the correlation coefficients of the pseudo-second-order adsorption kinetic model are significantly higher than those of the pseudo-first-order adsorption kinetic model. This indicates that the pseudo-second-order model can more accurately describe the adsorption behavior of the adsorbent on drugs in aquaculture tail water. Then, the equilibrium adsorption amount Q of the pseudo-second-order adsorption kinetics was calculated based on the model. e , the data are shown in Table 3. These calculated values ​​are consistent with the actual adsorption amount Q observed in the experiment eVery close, further verifying the accuracy of the quasi-secondary adsorption kinetic model. This shows that the adsorption of quinolones and tetracyclines by the adsorbent is mainly based on a chemical adsorption mechanism rather than simple physical adsorption. This chemical adsorption involves chemical bonding between the adsorbent and the target molecule, so it has a stronger binding force, which also involves electrostatic interactions, and chemical adsorption is the main reason for limiting the adsorption rate. At the same time, this also means that the adsorption process does not involve mass transfer in the solution, thereby further improving the adsorption efficiency and stability.

[0140] Embodiment 11

[0141] In the process of polymerization, the crosslinking agent is an important factor affecting the preparation of stable polymers. It has the function of controlling the polymer morphology and the stability and mechanical stability of the binding sites. Therefore, the amount of the binary crosslinking agent EGDMA with vinyl groups will also affect the adsorption capacity of HMP. The effect of the molar ratio of ATA to EGDMA on the adsorption capacity of the prepared HMP was investigated. The experimental method for determining the adsorption capacity of HMP is the same as that described in Example 10, and the adsorption capacity of the HMP prepared in Examples 4-8 is measured respectively.

[0142] The experimental results are as follows Figure 7 As shown in the figure, when the molar ratio of the two is 1:5, the adsorption capacity of HMP is the highest, and as the amount of EGDMA increases, the adsorption capacity decreases. This may be due to the fact that the excessively high concentration of EGDMA leads to a greater degree of cross-linking of the polymer, and the resulting spatial structure is relatively dense, rather than an ideal gel-type mesh pore structure. Therefore, the molar ratio of 1:5 is the optimal molar ratio of ATA / EGDMA. Under this condition, the spatial structure of HMP formed is looser and the specific surface area is larger, which makes the adsorption of HMP to the target molecule more sufficient and the internal mass transfer process is also faster.

[0143] Under the optimal molar ratio of ATA / EGDMA, the effect of polymerization reaction time on the adsorption capacity of the prepared HMP was investigated. The experimental method for determining the adsorption capacity of HMP was the same as that described in Example 10, and the adsorption capacity of the HMP prepared in Examples 6, 9-12 was determined respectively, wherein the initial drug concentration used was 0.5 μg / mL.

[0144] The experimental results are as follows Figure 8 As shown in the figure, with the increase of polymerization time, the adsorption capacity of HMP first increases and then decreases. When the polymerization time is 5h, ATA and EGDMA fully react, and the polymer layer formed at this time is an ideal gel-type mesh pore structure with the largest adsorption capacity. When the polymerization time exceeds 5h, the adsorption capacity decreases instead. This may be because the polymerization time is too long, resulting in excessive self-polymerization of ATA and the formation of a thicker polymer layer, which makes HMP have greater resistance to adsorbing target molecules. Therefore, 5h is selected as the optimal polymerization time for preparing HMP.

[0145] Example 12

[0146] The HMP prepared in Example 6 was added to aquaculture tail water, so that the antibiotic pollutants in the tail water were adsorbed on the surface of the material, thereby achieving the purpose of removal. The removal efficiency of HMP on antibiotic pollutants in actual aquaculture tail water was investigated.

[0147] 200 mL of aquaculture tail water was transferred, filtered through a 0.45 μm filter membrane, 25 mg of HMP was added, vortexed at 2000 r / min for 120 s, and the supernatant was obtained by magnetic separation. The pH value of the supernatant was adjusted to 4 with a 3% formic acid solution. 50 mL of the supernatant was transferred, 1.5 mL of methanol was added, and mixed for loading.

[0148] The Oasis HLB solid phase extraction column was pre-activated with 6 mL of methanol and 6 mL of water, and then loaded with sample, the flow rate was controlled at 4 mL / min, 5 mL of water was eluted, vacuum dried for 5 min, 8 mL of methanol was eluted, and all the eluents were collected in a glass test tube and blown to dryness with nitrogen at 45°C. 1 mL of pH 4.0 water-acetonitrile solution (8:2, V / V) was added and ultrasonically dissolved, and the mixture was filtered through a 0.22 μm filter membrane and then subjected to high performance liquid chromatography-tandem mass spectrometry.

[0149] The composition of antibiotic pollutants in actual aquaculture effluent and their removal rates are shown in Table 4.

[0150] Table 4 Removal efficiency of antibiotic pollutants in actual aquaculture tailwater

[0151]

[0152] It can be seen from Table 4 that:

[0153] (1) HMP has a significant adsorption effect on quinolone and tetracycline antibiotics.

[0154] (2) The adsorption performance of tetracycline antibiotics is better than that of quinolone antibiotics, and the actual measurement results are similar to those of the simulation experiment.

[0155] (3) After 120s vortex adsorption, the removal efficiency of antibiotic pollutants in aquaculture tail water can reach more than 65%. HMP has a high removal rate for antibiotic pollutants.

[0156] (4) The adsorption capacity of 25 mg HMP is lower than the maximum adsorption capacity of the static adsorption experiment in Example 10. This may be related to the fact that the actual tail water volume is large, the adsorption time is short, and HMP cannot be completely dispersed and adsorbed.

[0157] The results of practical applications show that the HMP provided by the present disclosure has both a high surface area and excellent magnetic saturation performance, strong hydrophilicity, and low synthesis cost, and has great application prospects in the removal of antibiotic pollutants in aquaculture tail water.

[0158] Embodiment 13

[0159] Characterization of the iron-aluminum MMH prepared in Example 2 and the MHP prepared in Example 6

[0160] X-ray diffraction (XRD)

[0161] There are four types of crystal structures of iron oxides, among which γ-Fe2O3 and Fe3O4 have roughly the same crystal structure and both belong to the inverse spinel structure. Fig. 9 shown.

[0162] pass Fig. 9 It can be seen that the two materials have diffraction peaks at 30.4°, 35.8°, 43.2°, 53.7°, 57.5° and 63.1°, which correspond to the six crystal planes (220), (311), (400), (422), (511) and (440) of γ-Fe2O3, respectively. The diffraction peaks at 21.3° and 36.8° correspond to the two crystal planes (110) and (311) of γ-Al(OH)3. The XRD results of HMP are very consistent with those of γ-Fe2O3 (39-1346) and γ-Al(OH)3 (7-0324), indicating that the products are γ-Fe2O3 and γ-Al(OH)3 with complete crystallization. The results show that the polymer layer is successfully coated on the surface of Fe-Al MMH. Since the surface of the Fe-Al-MMH particles in HMP is coated with a polymer layer, the intensity of all diffraction peaks of HMP is weaker than that of Fe-Al-MMH, but the physical structure of Fe-Al-MMH does not change during the polymerization process.

[0163] Fourier Transform Infrared Spectroscopy (FTIR)

[0164] The FTIR spectra of iron-aluminum MMH and HMP are as follows: Figure 1 As shown. 800cm -1 The following absorption peaks are caused by the stretching and bending vibrations of iron and aluminum oxides in FeAl MMH. -1 The broad peak between 1630cm -1 The characteristic absorption peak at 3200-3500cm is the OH bond vibration peak of water. From the FTIR spectrum of HMP, we can see that -1 Nearby (NH stretch), 1610-1660cm -1 Nearby (C=N) and 1318cm -1 、1260cm -1The peaks of (aromatic secondary amine) are all characteristic absorption peaks of ATA, while 950cm -1 、860cm -1 The characteristic absorption peak at is caused by the out-of-plane bending vibration of the CH substituted by triazole, which indicates that ATA is involved in the polymerization reaction.

[0165] 1728cm -1 (C=O stretching) and 1100-1200cm -1 The characteristic absorption peak of EGDMA near (COC stretching) confirms the presence of the crosslinker in the polymer.

[0166] FTIR spectrum results proved that HMP was successfully prepared.

[0167] Transmission electron microscopy (TEM) and scanning electron microscopy (SEM)

[0168] In order to further reveal the microscopic characteristics of the two materials, Fe-Al MMH and HMP, transmission electron microscopy and scanning electron microscopy were used to obtain high-resolution images of the two materials.

[0169] Fig.10 The following are TEM images of FeAl MMH and HMP. The morphological characteristics of the two were studied by transmission electron microscopy. Fig.10 As shown in (a), particles of different sizes and irregular shapes were observed in the TEM image of MMH. Fig.10 (a) Fig.10 (b) There is an additional light grey outer layer, which indicates that the polymer layer has been successfully prepared on the surface of the FeAl MMH. Fig.10 (c) It can be seen that after polymerization, the synthesized HMP has an obvious network pore structure.

[0170] Scanning electron microscopy was used to further analyze the morphology and size of the iron-aluminum MMH and HMP. Fig.11 As shown in (a), the FeAl MMH presents a spherical shape and is tightly aggregated together. Fig.11 As shown in (b), after polymerization, the HMP particles have irregular shapes and uneven sizes, and the particle size has also increased.

[0171] Magnetic properties analysis

[0172] The magnetic properties of iron-aluminum MMH and HMP were tested using a vibrating sample magnetometer.

[0173] Fig.12 It is the hysteresis curve (VSM) of iron and aluminum MMH and HMP. Fig.12It can be observed that both test materials present a centrally symmetrical state, which is a common characteristic of ferromagnetic materials. Further analysis shows that saturation magnetization and hysteresis loops appear in the curves. These two important features indicate that the prepared iron-aluminum MMH and HMP have superparamagnetic properties. Superparamagnetism is a special magnetic state that allows these materials to be quickly adsorbed by a magnet under the action of an external magnetic field and quickly lose their magnetism after the external magnetic field is removed. Specifically, the magnetization intensities of iron-aluminum MMH and HMP are 11.4 and 7.6 emu / g, respectively. This shows that with the increase of the polymer shell structure, the magnetic strength of the material gradually decreases. The reason for this decrease can be attributed to the shielding effect of the polymer shell on the surface of the iron-aluminum MMH, that is, the presence of the polymer shell weakens the material's ability to respond to the external magnetic field. Under the action of the external magnetic field, HMP can achieve rapid separation within 10s. This result fully proves that the polymer has good magnetic properties and can meet the needs of rapid separation in practical applications.

[0174] The present invention uses iron-aluminum MMH as a carrier, ATA as a functional monomer, EGDMA as a cross-linking agent, APS as an initiator, and water as a porogen to provide an HMP for adsorbing antibiotics in aquaculture tail water. Characterization and adsorption experiments have shown that the synthesized HMP has strong hydrophilicity and a fast adsorption rate, reaching adsorption equilibrium in 120s to 150s. The equilibrium adsorption capacity of HMP is 10.901 mg / g, and the adsorption of antibiotic pollutants in aquaculture tail water conforms to the quasi-second-order kinetic adsorption model, and the adsorption behavior is mainly chemical adsorption. HMP is applied to the treatment of antibiotic pollutants in actual aquaculture tail water. The detection and analysis results show that HMP can be quickly separated under a magnetic field, and the removal efficiency of antibiotic pollutants can reach more than 65%.

[0175] Therefore, HMP, which has a high specific surface area, excellent adsorption capacity and low preparation cost, is expected to become one of the outstanding removers of antibiotic pollutants in aquaculture effluent, and the novel green preparation method of HMP will provide new ideas for the development of better magnetic adsorption materials.

[0176] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.

Claims

1. A method for preparing a hydrophilic magnetic polymer, characterized in that: The preparation method comprises: Dissolving 3-amino-1,2,4-triazole in deionized water to obtain an aqueous solution of 3-amino-1,2,4-triazole; Adding the magnetic mixed hydroxide into deionized water, stirring continuously, adding the 3-amino-1,2,4-triazole aqueous solution after forming a suspension, continuing stirring for a period of time, then adding the crosslinking agent, continuing stirring for a period of time, and then adding the initiator to obtain a mixture; The mixture is transferred to an inert atmosphere environment, and a polymerization reaction is carried out in a water bath at 35-45° C. with stirring. After the reaction is completed, the product is collected by a magnet, and the product is washed and dried to obtain the hydrophilic magnetic polymer.

2. The preparation method according to claim 1, characterized in that The magnetic mixed hydroxide is a magnetic iron-aluminum mixed hydroxide.

3. The preparation method according to claim 2, characterized in that: The preparation method of the magnetic iron-aluminum mixed hydroxide comprises: Ammonium ferrous sulfate hexahydrate and aluminum chloride hexahydrate are completely dissolved in deionized water, and then an alkaline solution is added to adjust the pH value of the solution to 9.5-10.5, and a coprecipitation reaction is carried out under stirring conditions. After the reaction is completed, the product is collected by a magnet, and the product is washed to obtain the magnetic iron-aluminum mixed hydroxide.

4. The preparation method according to claim 3, characterized in that: The molar ratio of ammonium ferrous sulfate hexahydrate to aluminum chloride hexahydrate is not less than 2:

1.

5. The preparation method according to claim 1, characterized in that: The molar ratio of 3-amino-1,2,4-triazole to the cross-linking agent is 1:4.5-5.

5.

6. The preparation method according to claim 1, characterized in that: The polymerization reaction time is 4.5-5.5h.

7. A hydrophilic magnetic polymer, characterized in that The hydrophilic magnetic polymer has a mesh hole structure; The hydrophilic magnetic polymer comprises: A magnetic iron-aluminum mixed hydroxide and a polymer layer coated on the surface of the magnetic iron-aluminum mixed hydroxide, wherein the polymer layer is obtained by polymerization reaction of 3-amino-1,2,4-triazole aqueous solution and dimethyl glycol acrylate; The Fourier transform infrared spectrum of the hydrophilic magnetic polymer is shown in FIG1 .

8. Use of the hydrophilic magnetic polymer obtained by the preparation method according to any one of claims 1 to 6, or the hydrophilic magnetic polymer according to claim 7, in adsorbing antibiotic drugs in aquaculture tail water, characterized in that: The antibiotic drug is at least one of quinolone drugs and tetracycline drugs.

9. The use according to claim 8, characterized in that The antibiotic drug is a tetracycline drug.

10. The use according to claim 8, characterized in that The concentration of the antibiotic drug is not less than 0.8 μg / mL.

Citation Information

Patent Citations

  • Triazole gel material as well as preparation method and application thereof in adsorption of organic pollutants

    CN114653344A

  • Carbon-based magnesium-iron layered double-metal hydroxide adsorbent as well as preparation method and application thereof

    CN117046446A